MENGEMBANGKAN KETERAMPILAN GERAK DASAR SEBAGAI STIMULASI MOTORIK BAGI ANAK TAMAN KANAK-KANAK MELALUI AKTIVITAS JASMANI - Cerika Rismayanthi (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2013)
Developments in early childhood include physical and motor development, cognitive, social emotional and language.Kindergarten Period (TK) is the most intense period of growth and the busiest. At this time the child already has theskills and ability even though not perfect. Age of the child at this time is a fundamental phase that will determine thefuture life. Therefore, as parents and educators need to understand the development of early childhood particularphysical and motor development. Motor development is strongly influenced by the organs of the brain, stimulatinggrowth through play occurs when a child’s muscles jumping, throwing, or running. In addition, children play withusing all the emotions, feelings, and his mind. Education in kindergarten implemented the principle of “Play whilelearning, or learning while playing “. In accordance with the development , and therefore expected an educatorwhose creative and innovative so that the child can feel happy , calm , safe and comfortable during the learningprocess . Basic motor competence of kindergarten children are expected to be developed when the child is enteringkindergarten children are able ; physical activity in a coordinated manner in order to flexibility and preparation forwriting , balance , agility , and courage train . Express them and be creative with ideas and imagination and use avariety of media / materials into a work of art.Keywords: Basic Movement Skills, Stimulation of Motor, Physical Activity.